Vascular endothelial growth factor: a key factor in the onset and treatment of depression - Wang, Jing; Meng, Fanhao; Wang, Long; Li, Zeguang (Frontiers in Cellular Neuroscience, 2025)
BackgroundMajor depressive disorder (MDD) is a common chronic psychiatric disorder that affects individuals of all ages worldwide, causing significant impairment to patients’ physical and mental health as well as social functioning. Vascular endothelial growth factor (VEGF), traditionally recognized as a regulator of angiogenesis and vascular permeability, has been identified in recent studies to possess neurotrophic and neuroprotective potential in the central nervous system (CNS) and is implicated in the pathological processes of MDD.AimTo systematically elaborate on the role of VEGF in the pathological mechanisms of MDD and its potential as a target for antidepressant therapy.Key findingsThrough interactions with its receptors (VEGFR1, VEGFR2, and VEGFR3), VEGF regulates critical pathways such as gene expression, blood-brain barrier (BBB) function, and brain-derived neurotrophic factor (BDNF), thereby establishing physiological and pathological associations with MDD. Its signaling pathway serves as a core target for various antidepressant treatments, including conventional antidepressants, ketamine, electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), and resolvins. Short-term upregulation of central VEGF may exert antidepressant effects by promoting the benign remodeling of neurovascular networks, and its subsequent return to baseline levels during treatment can avoid BBB damage, providing novel insights for the management of rapid-onset and treatment-resistant depression.ConclusionVascular endothelial growth factor holds significant importance in the pathology and treatment of MDD. In-depth exploration of its regulatory mechanisms may provide a basis for the development of novel antidepressant therapies.